ANALISIS WAKTU TUNGGU PENDISTRIBUSIAN BERKAS REKAM MEDIS PASIEN RAWAT JALAN GUNA MENINGKATKAN MUTU PELAYANAN REKAM MEDIS DI RSUP Dr. HASAN SADIKIN BANDUNG - Luqman Nul Hakim; Wowo Trianto (UPPM Politeknik TEDC Bandung, 2020)
The implementation of good medical record system, one of which must be supported by medical record file distribution system. The distribution of a good medical record file is distributed medical record file is fast, precise and efficient. The distribution of medical record file must be able to support the health services, particularly subject to outpatient quality services. Therefore, we need an reviews adequate the distribution of health services officers that can runs is well and smoothly. The authors uses a descriptive of research method.With the population of all patients visiting outpatient long march in 2015 as many as 30 068 patients, the total sample of 396 files.The results of the study are still delays in the distribution of medical records at the RSUP Dr. Hasan Sadikin Bandung abotained with the average was length of time of 32 minutes for each file, among of others diligence to lack of personnel, especially medical records of storage sevice sections that does not close of the of storage space, causing delays in the distribution of medical records to the service unit. That requires officers special of storage section so other officers can complete of the tasks and responsibilities of each, of the authors also suggest that use of “Pneumatic Tube